A comparative analysis of carbon reduction potential for directly driven permanent magnet and doubly fed asynchronous wind turbines. Issue 3 (23rd February 2023) - Zhuo, Zhi‐Yu; Chen, Meng‐Jie; Li, Xiu‐Yu
Abstract: Wind power generation does not emit greenhouse gases or pollutants, but there are some carbon emissions from the manufacturing, transportation, operation, and waste disposal of wind turbines. Directly driven permanent magnet and doubly fed asynchronous wind turbines currently have the largest market share in China, but few Chinese studies have compared their differences in carbon reduction potential. This paper uses life cycle assessment (LCA) to quantitatively analyze the full life cycle carbon emissions of the two wind turbines to determine which type of wind turbine has greater carbon reduction potential, obtaining the following results. (1) The full life cycle greenhouse gas emissions of 2.5 MW directly driven permanent magnet and doubly fed asynchronous wind turbines are 8.48 and 10.43 g CO2 /kWh, respectively. The direct‐driven permanent magnet wind turbine is superior in terms of carbon reduction. (2) The stage with the greatest impact and the greatest difference between the two wind turbines in the full life cycle is the production stage, during which the carbon emissions of the directly driven permanent magnet and doubly fed asynchronous wind turbines are 1.045 × 10 6 and 1.210 × 10 6  kg, respectively. (3) According to sensitivity analysis, proper waste disposal and transportation can reduce carbon emissions from wind turbines. These research findings can be used to help achieve carbon peaking and neutrality goals, as well as the technological development of wind power enterprises. Abstract : Specifically targeting directly driven permanent magnet and doubly fed asynchronous wind turbines, this paper uses life cycle assessment to quantitatively analyze the full life cycle carbon emissions of two types of wind turbines. This study is helpful to understand the differences in the potential of different types of wind turbines in mitigating the greenhouse effect and reducing carbon emissions. The research results provide some reference for the realization of China's carbon peaking and carbon neutrality goals and the technological development of wind power enterprises.